Multicultural Islamic Religious Education Curriculum for Students with Intellectual Disabilities: Implementasi Kurikulum Pendidikan Agama Islam Multikultural bagi Siswa Tunagrahita - Fitriani, R. Nurul; Futaqi, Sauqi; Rahmawati, Zuli Dwi (Universitas Muhammadiyah Sidoarjo, 2025)
This study aims to analyze the implementation of a multicultural-based Islamic Religious Education (PAI) curriculum for students with intellectual disabilities at SLB Negeri Lamongan. This research employs a qualitative method with a descriptive approach through observation, interview, and documentation techniques. The findings indicate that SLB Negeri Lamongan has established a learning environment that respects student diversity and has adapted the PAI curriculum to the characteristics of students with intellectual disabilities. Adaptations include the formulation of realistic learning outcomes, individualized teaching methods, and the use of engaging and adaptive learning media. Religious values are taught applicatively through direct practice, and curriculum evaluation is carried out continuously, involving various stakeholders and emphasizing students’ affective and psychomotor development. The theoretical contribution of this research lies in emphasizing the importance of multicultural and individualized approaches in religious education for students with special needs. Its practical implications highlight the need for inclusive and adaptive curriculum development, as well as teacher training to design instruction that meets students’ specific needs. The limitation of this study is its focus on a single school with a limited number of participants. In conclusion, multicultural and individualized approaches in Islamic education are proven to be strategic in creating equitable and transformative education. It is recommended that similar studies be conducted in other schools to broaden the generalization of findings and to support policies promoting inclusive education. Highlights: Emphasizes adaptive PAI curriculum for students with intellectual disabilities. Promotes multicultural and inclusive teaching practices. Recommends broader studies to support inclusive education policy. Keywords: PAI Curriculum, Multicultural Education, Intellectual Disabilities